Foreign investment, institutional quality, public expenditure and activity of venture capital funds in emerging countries (2013)
This paper is an empirical analysis of the effects of foreign direct investment (FDI), institutional quality and the size of a government on venture capital (VC) activity. We conclude that institutional quality, the FDI and public spending have definitive importance as elements for the development of a public policy that increases the quantity and quality of venture capital fund (VCF) investment. Higher institutional quality, higher FDI and lower public spending allow the VCF investment volume to grow. The FDI shows higher level of significance in promoting investment in high-tech companies and institutional quality increases the productivity of FDI investment in the generation of VCF. Government spending dramatically and adversely affects the activity of VCF and institutional quality increases the negative effect of government spending on the activity of VCF in emerging countries. This last result suggests that the higher the institutional quality of a country, the less state intervention it requires to promote investment of VCF. The results are consistent with the hypothesis of the FDI spillover and crowding out of public spending.